THE Academic Vocabulary and Technology: Academic Vocabulary and Technology - Jo’rayev, Muhammadrahimxon (Maktabgacha taʼlim jurnali, 2021)
Educators can plan a whole session using modern technologies such as power point can be used to explain new theme and students can swap in formation in-in-session with their fellow students or their teachers, etc. “On the account of the wide variety of information that can that can be viewed online, the sources and links must be carefully selected and introduced, and the teachers must monitor students so that they will not drift off and lose focus.